Progressive Prosecution Policies in Philadelphia: An Assessment of Implementation Fidelity - Ward, Jeffrey T. (American journal of criminal justice, 2025)
Contemporary prosecutor-led criminal justice reform seeks to improve fairness and reduce the justice system footprint. To this end, “progressive” prosecutorial offices have adopted numerous policies that set presumptive actions and guide attorney decision making. We develop a measure of justice policy implementation fidelity that enables an overall assessment of the implementation of a collection of recent prosecutorial policies in Philadelphia tapping into several domains: support, clarity, beliefs, monitoring, barriers, and adherence. Data were collected during 2021–2022 from a sample in the Philadelphia District Attorney’s Office (DAO) and were analyzed using reliability and principal-components factor analysis, tabular and data visualization methods, and OLS regression. Results indicate generally strong support for and adherence to progressive policies. However, policy clarity is moderate, and there are internal barriers perceived to adversely affect implementation efforts. DAO staff believe policies are generally effective for addressing unfair outcomes for defendants, but less so with more traditional system aims, such as decreasing crime rates and achieving quick case resolution. Adherence can be bolstered by improving other elements of implementation fidelity. These findings provide important guidance for both future policy implementation efforts in Philadelphia and for DAs seeking to implement reform agendas in other locales.